Demonstrating Dilute-Tin Alloy SiGeSn for Use in Multijunction Photovoltaics: Single- and Multijunction Solar Cells With a 1.0-eV SiGeSn Junction - Roucka,R; Clark,A; Wilson,T; Thomas,T; Fuhrer,M; Ekins-Daukes,N; Johnson,A; Hoffman,R; Begarney,D (IEEE Journal of Photovoltaics, 2016)
SiGeSn ternary alloys offer a means to fabricate a 1.0-eV subcell junction for inclusion in a multijunction solar cell. The main advantage of the SiGeSn alloy is a tuneable bandgap energy and variable lattice parameter, enabling the material to be integrated into the existing lattice-matched multijunction architectures. Recent growth, structural, optical, and device results from SiGeSn material, with energy gaps in the vicinity of 1.0 eV and lattice matched to Ge substrates, are presented. An all lattice-matched InGaP/InGaAs/SiGeSn triple-junction cell is presented and compared with a conventional InGaP/InGaAs/Ge solar cell. Comparable short-circuit current values of 13.9 mA/cm2 are obtained for both devices under the AM1.5G spectrum, whereas the open-circuit voltage and fill factor are reduced in the device with the SiGeSn subcell. Peak external quantum efficiency in the SiGeSn single junction in excess of 80% is realized, placing a lower limit on the base minority hole diffusion length of 5 μm with surface recombination velocities in close agreement to those found in bulk Ge material.